2015
DOI: 10.3389/fpsyg.2015.01102
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the use of personally relevant stimuli for investigating patients with disorders of consciousness

Abstract: Sensory stimuli are used to evaluate and to restore cognitive functions and consciousness in patients with a disorder of consciousness (DOC) following a severe brain injury. Although sophisticated protocols can help assessing higher order cognitive functions and awareness, one major drawback is their lack of sensitivity. The aim of the present review is to show that stimulus selection is crucial for an accurate evaluation of the state of patients with disorders of consciousness as it determines the levels of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 105 publications
(116 reference statements)
3
54
0
2
Order By: Relevance
“…There are several limitations to the NSE method and its translation to clinical practice. In our study, we utilized personalized narratives that were recorded by the patient's family members; prior studies have demonstrated that personal and meaningful stimuli elicit more robust and reliable auditory responses in brain-injured patients [45]. However, acquiring personalized narratives imposes an additional time constraint relative to the use of standardized stimuli.…”
Section: Individual Nse Responsesmentioning
confidence: 99%
“…There are several limitations to the NSE method and its translation to clinical practice. In our study, we utilized personalized narratives that were recorded by the patient's family members; prior studies have demonstrated that personal and meaningful stimuli elicit more robust and reliable auditory responses in brain-injured patients [45]. However, acquiring personalized narratives imposes an additional time constraint relative to the use of standardized stimuli.…”
Section: Individual Nse Responsesmentioning
confidence: 99%
“…34 This might be a mechanism underlying the here documented effects of DAT, since studies have illustrated that personally and emotionally relevant stimuli induce higher-level activation in DOC patients with disorders of consciousness. 35,36 The high motivation to interact with an animal might also be based on the fact that caregiving is a core need of humans and forms a central part within attachment theory. 37 Caring for an animal is highly emotionally relevant for many people, since this need has been biologically relevant throughout human evolution.…”
Section: Discussionmentioning
confidence: 99%
“…It turns out that researchers have provisionally attempted to assess residual emotional function in some patients. But no systematic attempt to assess levels of emotional functioning has been conducted (see Perrin, Castro, Tillmann, and Luauté 2015 ). As a result, although it is known that patients with traumatic brain injuries retain some capacity for functional response to emotional and self-relevant stimuli, the level or complexity of their emotional lives is not well understood.…”
Section: Case One: Traumatic Brain Injurymentioning
confidence: 99%